PERAN KELUARGA, TOKOH MASYARAKAT DAN KADER DENGAN KELENGKAPAN IMUNISASI DASAR - Nita Tri Putri (Maternal Child Health Care, 2022)
The World Health Organization (WHO) states that of its 194 member countries, 65 of them have complete basic immunization coverage below the global target of 90%. According to the Indonesian Ministry of Health (2016) Complete Basic Immunization (IDL) reached 86.8%. The purpose of this study was to determine the relationship of the role of families, community leaders and cadres with the completeness of basic immunization for toddlers 11-12 months in the work area of Padang Alai Health Center Padang Pariaman District in 2018.The research design used was descriptive analytic with cross sectional design. The study was conducted in August 2018 in the Padang Alai Community Health Center Work Area. The population of mothers who have infants aged 11-12 months, as many as 256 people. Samples were taken as many as 71 people with random sampling technique.The results of the study showed that 59.2% of the family's role was low, 52.1% of the role of community leaders were negative, 63.4% of the cadre's role was still low, 70.4% did not provide complete basic immunization to their children. There was a significant relationship between family roles by providing basic immunization complete with p value 0.009. There is a significant relationship between the role of community leaders with the provision of basic immunization complete with p value 0.005. There is a significant relationship between the role of cadres with basic immunization complete with p value 0.009.Based on the results of the study, it can be concluded that the maximum basic immunization for infants is not yet optimal due to the lack of family roles, the role of community leaders and also the role of cadres. It is expected that village officials (posyandu officers) should be more intensive in conveying information to the community. Should collaborate with community leaders, traditional leaders in providing counseling to the public about the importance of complete basic immunization in children.Keywords     : Role of Families, Role of Community Leaders, Role of Cadres,Complete Basic Immunization